The Diversity of Macroalgae Species with Prospects for Medicinal Applications in Aquatic Environments - Shobir, Haris; Triastinurmiatiningsih, Triastinurmiatiningsih; Ismanto, Ismanto (Universitas Pakuan, 2025)
Macroalgae are important marine organisms known to contain polysaccharides such as alginate, agar, and carrageenan, as well as bioactive compounds and pigments with significant pharmaceutical potential. This study aimed to identify and analyze the diversity of macroalgae species that have potential medicinal properties in the coastal waters of Cidatu Beach, Pandeglang Regency, Banten Province, Indonesia. The research employed a transect method with three sampling stations along the intertidal zone. At each station, three transects were established 5 meters apart, and each transect contained five 1×1 m plots separated by 5 meters. A total of 12 macroalgae species were identified, comprising three species of Chlorophyceae (Ulva intestinalis, Ulva reticulata, Chaetomorpha crassa), five species of Phaeophyceae (Padina australis, Turbinaria conoides, Turbinaria decurrens, Sargassum polycystum, Sargassum crassifolium), and four species of Rhodophyceae (Gracilaria salicornia, Gracilaria coronopifolia, Gelidium sp., Amphiroa fragilissima). The Shannon–Wiener diversity index (H′) of 2.169 indicates a moderate level of species diversity in the study area. Environmental conditions such as temperature (29–30°C), salinity (31–32‰), and pH (7.0) were within the optimal range for macroalgal growth, although light intensity was relatively low (1,939 lux). Based on literature analysis, ten of the recorded species demonstrated potential pharmacological value, exhibiting antibacterial, antifungal, antiviral, antitumor, antihypertensive, and antihemorrhagic properties. Among these, species of Sargassum, Padina, and Gracilaria are particularly noteworthy for their bioactive compounds, including tannins, flavonoids, and polysaccharides. The moderate diversity and high medicinal potential of the identified macroalgae suggest that Cidatu Beach supports a rich yet underutilized marine biota. Further biochemical and pharmacological investigations are recommended to explore their potential as sustainable sources of natural medicinal compounds.